Kelengkapan Resume Medis dan Keakuratan Kode Diagnosa Kasus Perinatal di Rumah Sakit Panti Waluya Malang - Cecilia Widijati Imam; Nanta Sigit; Raswati Prapti Rahayu (FORUM ILMIAH KESEHATAN, 2022)
Health service facilities that run medical services are required to always provide quality services. One indicator of the completeness of services is a medical record with a complete medical resume. This study used secondary data obtained from medical records of perinatal patients at Panti Waluya Hospital, Sawahan, Malang in 2021. The study design was cross-sectional. The sample was 44 medical record files. The data were analyzed using the Spearman Rank test. The results showed that there was a significant relationship between the completeness of the medical resume and the accuracy of the diagnostic code for perinatal cases. If a medical resume is complete, the resulting perinatal case diagnosis code is more accurate.Keywords: medical resume; coders; perinatal ABSTRAK Fasilitas pelayanan kesehatan yang menjalankan pelayanan medis dituntut untuk selalu memberikan mutu pelayanan berkualitas. Salah satu indikator kelengkapan pelayanan adalah rekam medis dengan kelengkapan resume medis. Penelitian ini menggunakan data sekunder yang diperoleh dari rekam medis pasien kasus perinatal di RS Panti Waluya, Sawahan, Malang tahun 2021. Desain penelitian adalah cross-sectional. Sampel adalah 44 berkas rekam medis. Data dianalisis menggunakan uji Spearman Rank. Hasil penelitian menunjukkan bahwa terdapat hubungan yang signifikan antara kelengkapan resume medis dengan keakuratan kode diagnosa kasus perinatal. Jika suatu resume medis lengkap, maka kode diagnosa kasus perinatal yang dihasilkan semakin akurat.Kata kunci: resume medis; coder; perinatal